The Role of Homeroom Teacher in Guidance and Counseling Services at School - Rif’aty Nizhomy; Daharnis Daharnis (Jurnal Neo Konseling, 2022)
The homeroom teacher has a greater daily intensity contact with students than the counselor teacher.  The study aimed to describe the homeroom teacher role in Guidance and Counseling services at school. This research used descriptive quantitative research method. The subjects in this study were 24 homeroom teachers at Junior High School 25 Padang in the 2021/2022 school year. The data were collected by questionnaires on the homeroom teacher role in Guidance and Counseling services at the school. The result showed that the role of the homeroom teacher in Guidance and Counseling services in schools as a whole was in the high category which broken down into eight aspects: 1) Helping counselor teacher carried out their duties, was in the high category. 2) Helping counselor teacher identified students who needed BK services, was in the high category. 3) Transferring students who needed counseling services from counselor teacher, was in the high category. 4) Accepting the transferred students from counselor teacher who required special training services such as enrichment, was in the high category. 5) Helping in developing a classroom atmosphere; teacher-student relationships, and student-student relationships that supported the implementation of counseling services, was in the high category. 6) Helping in providing opportunities and convenience to students who needed counseling services, was in the high category. 7) Participating in counseling activities, especially in handling student problem such as case conferences, this was in the high category. 8) Assisting in collecting the information needed in the context of evaluating counseling services as a follow-up effort, was in the very high category. Based on the results of this study, the suggested services that can be provided to increase the role of the homeroom teacher in the implementation of Guidance and Counseling were information services that mastering individual counseling content and services.